Translation but not the encoded sequence is essential for the efficient propagation of the defective interfering RNAs of the coronavirus mouse hepatitis virus. - van der Most, R G (1995)
The defective interfering (DI) RNA MIDI of mouse hepatitis virus strain A59 (MHV-A59) contains a large open reading frame (ORF) spanning almost its entire genome. This ORF consists of sequences derived from ORF1a, ORF1b, and the nucleocapsid gene. We have previously demonstrated that mutations that disrupt the ORF decrease the fitness of MIDI and its derivatives (R. J. de Groot, R. G. van der Most, and W. J. M. Spaan, J. Virol. 66:5898-5905, 1992). To determine whether translation of the ORF per se is required or whether the encoded polypeptide or a specific sequence is involved, we analyzed sets of related DI RNAs containing different ORFs. After partial deletion of ORF1b and nucleocapsid gene sequences, disruption of the remaining ORF is still lethal; translation of the entire ORF is not essential, however. When a large fragment of the MHV-A59 spike gene, which is not present in any of the MHV-A59 DI RNAs identified so far, was inserted in-frame into a MIDI derivative, translation across this sequence was vital to DI RNA survival. Thus, the translated sequence is irrelevant, indicating that translation per se plays a crucial role in DI virus propagation. Next, it was examined during which step of the viral life cycle translation plays its role. Since the requirement for translation also exists in DI RNA-transfected and MHV-infected cells, it follows that either the synthesis or degradation of DI RNAs is affected by translation.